Enkapsulasi minyak atsiri lemon (Citrus limon) menggunakan penyalut β-siklodekstrin terasetilasi (Sebuah Review). - Fanny Dhea Suryafly; Isna Rasdianah Aziz (Prosiding Seminar Biologi, 2019)
Lemon oil (Citrus limon) is an essential oil that is useful in the field of aromatherapy. Lemon oil is useful for reducing stress and refreshing the mind by breathing in the vapors. Essential oils are generally susceptible to high temperatures, oxidation, UV rays, and humidity, causing oxidative damage. Encapsulation can provide solutions to these problems. β-Cyclodextrin is a good coating in the encapsulation of essential oils. This paper will discuss the encapsulation of lemon oil using β-cyclodextrin acetylated. The catalyst used for the β-cyclodextrin acetylation reaction was beta zeolite which was modified with Zr4 + metal by ion exchange method.